Ectopic Overexpression of PPARγ2 in the Heart Determines Differences in Hypertrophic Cardiomyopathy After Treatment With Different Thiazolidinediones in a Mouse Model of Diabetes - Cao, Xuemei; Mao, Min; Diao, Junlin; Hou, Yi; Su, Hong; Gan, Yongjun; Li, Jibin; Tong, Xiaoyong; Wu, Chaodong; Zuo, Zhong; Xiao, Xiaoqiu (Frontiers in Pharmacology, 2021)
The clinical controversy of rosiglitazone as a hypoglycemic agent is potentially associated with heart failure, mainly due to its potent activation of peroxisome proliferator-activated receptor γ (PPARγ). PPARγ partial agonists showed superior pharmacological profiles to rosiglitazone. This study compared differences in cardiac morphology and function of the PPARγ partial agonist CMHX008 with rosiglitazone. High-fat diet (HFD) induced obese mice, ob/ob mice and cardiomyocytes overexpressing PPARγ2 were treated with CMHX008 or rosiglitazone. Heart function, myocardial morphology, and hypertrophy-related gene expression were examined. Clinical information from patients with type 2 diabetes mellitus (T2DM) who had taken rosiglitazone and undergone Doppler echocardiography was collected. HFD and ob/ob mice significantly developed cardiac contractile dysfunction, with upregulated PPARγ2 protein levels in heart tissues. Cardiomyocytes of HFD and ob/ob mice were disorderly arranged, the cell areas expanded, and collagen accumulated. In vitro cardiomyocytes overexpressing PPARγ2 displayed obvious structural abnormalities and high mRNA levels of ANP and BNP, critical cardiac hypertrophy-related genes. HFD-fed mice treated with rosiglitazone or CMHX008 had significantly improved cardiac function, but rosiglitazone induced higher expression of ANP and BNP and hypertrophic cardiomyopathy, while CMHX008 did not. Patients with T2DM taking rosiglitazone exhibited increased thickness of the posterior wall and the ventricular septum, suggesting cardiac hypertrophy. Our findings show that diabetic cardiomyopathy was associated with ectopic overexpression of PPARγ2. The full agonist rosiglitazone prevents cardiac dysfunction at the expense of compensatory hypertrophy, while the partial agonist CMHX008 shared a comparable protective effect without altering the structure of cardiomyocytes.